2021
DOI: 10.1590/1516-3180.2020.0635.150321
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cognitive impairment among individuals aged 60 years or over: scoping review

Abstract: Although substantial increases in the numbers of elderly people are now foreseen in all countries, greater growth is expected in developing regions such as Brazil, where the proportions are expected to become 18.8% in 2020 and 29.3% in 2050. 1,2 Primary care is considered to be the front line for healthcare for the elderly and can provide regular contacts focused on preventing disabilities resulting from chronic health conditions, such as classification of cognitive impairment in this age group. 3 Healthcare p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that physical activity (PA) can slow cognitive decline 7–9 . Multidomain intervention study protocols involve strategies such as blood pressure control, promotion of PA, and management of other risk factors to assess their combined impact on reducing the risk of dementia 10–12 . Yet the optimal volume and intensity of PA required for this benefit remain unclear 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that physical activity (PA) can slow cognitive decline 7–9 . Multidomain intervention study protocols involve strategies such as blood pressure control, promotion of PA, and management of other risk factors to assess their combined impact on reducing the risk of dementia 10–12 . Yet the optimal volume and intensity of PA required for this benefit remain unclear 8 .…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 , 9 Multidomain intervention study protocols involve strategies such as blood pressure control, promotion of PA, and management of other risk factors to assess their combined impact on reducing the risk of dementia. 10 , 11 , 12 Yet the optimal volume and intensity of PA required for this benefit remain unclear. 8 Furthermore, uncertainties persist regarding the combined impact of PA intensity levels, the influence of baseline PA, and the shape of the dose‐response curve on the protective effects of PA on cognition.…”
Section: Introductionmentioning
confidence: 99%
“…These deficits in everyday functioning may be further associated with problems in independent living, working, self-care, and socializing ( 6 ). Hence, everyday functioning is not only an important marker for screening cognitive alterations ( 7 ) but also a therapeutic target for rehabilitation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of VFS is similar to Folstein’s Mini Mental State Examination test ( 9 ), but is free of charge and the levels of resistance or refusal to participate are low because listing words for 1 min is not particularly intimidating. It does not require any materials other than a device to keep track of the time and a means for recording the number of words produced ( 10 ). VFS also has been used previously as single cognitive measure in large population based studies ( 11 ).…”
Section: Introductionmentioning
confidence: 99%